PKM Pemberdayaan Kelompok Tani Pembudidaya Ikan Lele - Andi Puspa Sari Idris; Subariyanto Subariyanto; Patang Patang (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2022)
This PKM aims to improve the knowledge and skills of catfish farmers in carrying out catfish farming activities properly. Pao-Pao Village is one of the villages located in Tanete Rilau District, Barru Regency and South Sulawesi. This village is well known as a fishing area in South Sulawesi, especially catfish farmers. Catfish farming has been carried out by the community in this village, that is managed by a concrete pond system or cultivation in rice fields /ponds. Through this training activity, catfish farmers can already cultivate catfish not only using a concrete pool that has been done so far, but also can cultivate catfish with a tarpaulin pond system and can make homemade pellet feed. The training methods used include problem identification, solution design, material giving, question and answer, hands-on practice, mentoring and activity evaluation. In this training activity, partner communities have been trained to cultivate catfish with plastic tarpaulin system fish farming and how to make artificial feed. After attending the training, the partner communities have been able to cultivate catfish with a tarp pool system and able to make homemade feed pellets.